Epidemiology of peste des petits ruminants in Uganda - Nkamwesiga, Joseph (Freie Universität Berlin, 2024)
Peste des petits ruminants (PPR) is a viral disease that affects domestic small ruminants (goats and sheep) and some wild small ruminants. By 2015, more than 70 countries in Africa and Asia were confirmed as affected although the threat to Europe through Turkey and Bulgaria was quickly neutralised. In Uganda, PPR was first reported in 2007 the Karamoja subregion of northeastern Uganda in 2007, a region comprised of 9 different districts. PPR persisted in this region. Upon eradication of Rinderpest in 2011, PPR was identified as the next target for eradication because of how closely related their aetiologies and epidemiological situations were. Indeed, in 2016, the Food and Agriculture Organization of the United Nations (FAO) and the World Organisation for Animal Health (WOAH) launched a four-stage global PPR control and eradication (PPR-GCEP) by 2030. The control plan was set up to leverage on the momentum gained from PPR control activities to tackle other small ruminant diseases identified by small ruminant keepers through joint activities such as concurrent vaccination against multiple diseases. The PPR-GCEP demands that every PPR affected country complies with the program and implements respective activities to warrant progression from one stage to another until PPR is eradicated following a self-administered PPR Monitoring and Assessment Tool (PMAT). After all steps are achieved, countries will apply for declaration of freedom from disease and continue with activities aimed at maintenance of disease-free status. This thesis was designed to update the PPR epidemiological situation in Uganda, by generating data to fit into PPR-GCEP stage 1 (assessment stage) as well as identify areas for targeting of interventions – which is the cornerstone for the PPR-GCEP stage III (control stage), activities that directly contribute the PPR-GCEP. To achieve the set objectives, this study employed a range of advanced epidemiology, and social network analysis techniques to analyse archived PPR outbreak data and small ruminants movement data respectively. Additionally, the study employed molecular biology and molecular epidemiology techniques to identify the circulating PPR virus and other relevant coinfections in all cases of PPR-like disease reported in Uganda during the study period (202-2022).